Weed Vegetation Analysis in Lowland Rice Cultivation in South Minahasa Regency - Orbanus Naharia (Journal of Innovative and Creativity, 2025)
Goal. This study aims to analyze the composition, dominance structure, and temporal changes of weed vegetation in lowland rice cultivation in South Minahasa Regency. The research specifically seeks to identify dominant weed species at the initial observation, 21 days after sowing (DAS), 45 DAS, and 60 DAS, as a basis for determining appropriate weed management strategies during the rice growth cycle. aterials and methods. Weed vegetation analysis was conducted using the parameters of Absolute Density (AD), Relative Density (RD), Absolute Frequency (AF), Relative Frequency (RF), Absolute Dry Weight (ADW), and Relative Dry Weight (RDW). These values were integrated to obtain the Species Dominance Ratio (SDR) at four observation stages. Weed sampling was carried out using standard quadrat methods, and dry weight was determined after oven-drying samples at 80°C for 72 hours. The results showed that weed composition changed dynamically across growth phases. At the initial observation, the highest SDR values were recorded for Paspalum distichum, Marsilea crenata, Fimbristylis litoralis, Cyperus iria, and Ludwigia octovalvis. At 21 DAS, dominant weeds were P. distichum, Leersia hexandra, M. crenata, and Echinochloa crus-galli. At 45 DAS, P. distichum, E. crus-galli, L. octovalvis, and L. hexandra maintained dominance, while at 60 DAS, E. crus-galli became the most dominant species, followed by L. octovalvis, Limnocharis flava, and P. distichum. Overall, grass-type weeds showed consistently high RD, RF, and RDW values, indicating strong competitive ability throughout the rice growth cycle. The findings confirm that weed dominance in lowland rice is strongly influenced by crop growth stage, canopy development, and the competitive traits of individual weed species. Grass weeds, particularly E. crus-galli and P. distichum, demonstrate high adaptability and resource-use efficiency, making them persistent competitors in rice ecosystems. These findings reinforce the need for timely and stage-specific weed management interventions, especially during the critical period of 3–8 weeks after planting, to prevent significant yield loss and to support sustainable rice production in South Minahasa Regency.